A review of nutritional profile and processing of faba bean (Vicia faba L.). Issue 3 (28th October 2021) - Dhull, Sanju Bala; Kidwai, Mohd. Kashif; Noor, Rashed; Chawla, Prince; Rose, Pawan Kumar
Abstract: Faba bean ( Vicia faba L.), a nutritious leguminous cool tolerant crop, is widely cultivated throughout the world. China, Ethiopia, the United Kingdom, Australia, and France are the main producers of faba beans. In recent years, interest has been growing in health and nutritional benefits of faba beans and developments of different foods enriched with biomolecules with improved functionality, nutrition value, and health benefits. Faba beans are rich source of lysine rich proteins, carbohydrate, minerals, vitamins, and numerous bioactive compounds. It is also a good source of l‐3, 4‐dihydroxyphenylalanine (L‐DOPA), which is a precursor of dopamine and can be potentially utilized for Parkinson's disease treatment. The seeds of faba beans can be consumed dry, roasted, soaked, cooked, frozen, or canned. However, a number of antinutritional factors such as phytic acid, trypsin inhibitors, saponins, vicin and convicine (favism‐inducing compounds), lectins, and condensed tannins negatively affect the biological value of faba beans resulting in its underutilization. For expanding the utilization of faba beans in human nutrition, the removal of these antinutrients is necessary. A number of methods including dehulling, soaking, germination, fermentation, and heat processing (cooking, boiling, extrusion, and autocalving) have been used individually or in combination to eliminate or destroy the antinutritional factors in faba beans. This comprehensive review covers global production, nutritional profile, and processing of faba beans and its utilization in various product developments.